(untitled) (INMR - Innovation & Management Review, 2015)
The present study sought to describe how to use the Business Model Generation in entrepreneurship classes, aiming to present the methodology used to apply the model in the classroom and students' perceptions about the use of a practical model for learning. A review of the literature was about the model itself and its background and then described in the application of the Business Model Generation in the discipline of entrepreneurship at the Faculdade de Economia e Administração, Universidade de São Paulo. Qualitative interviews were conducted with groups of students, in the total of fourteen, verifying that they approved the initiative and highlighted the strengths and weaknesses of the application of the model in the classroom. In addition, was presented the perception of teachers on the use of the model. This is a descriptive, qualitative study, considered as a teaching case. It may contribute to undergraduate teaching in the decision to use the model in a classroom, and promote the initiation of research on issues related to the model, since there are few academic efforts made in this direction.